2015
DOI: 10.1590/s0100-204x2015000800008
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance to preharvest sprouting and yield of wheat genotypes from different breeding programs

Abstract: -The objective of this work was to characterize the performance of elite wheat genotypes from different Brazilian breeding programs for traits associated with grain yield and preharvest sprouting. The study was conducted in 2010 and 2011 in the municipality of Capão do Leão, in the state of Rio Grande do Sul, Brazil, in a randomized complete block design with three replicates. Thirty-three wheat genotypes were evaluated for traits related to preharvest sprouting and grain yield. The estimate of genetic distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The cultivar Frontana was introduced in 1940, descended from the crossing between Fronteira and Mentana, when it conferred resistance to leaf rust and pre-harvest sprouting. Cultivar Frontana is one of the best sources of tolerance pre-harvest sprouting (Franco et al, 2009;Santos et al, 2010;Nörnberg et al, 2015). The Ônix/CDFAPA 2001129 and Vanguarda/Temu 2624-00, parents are responsible for good tolerance to pre-harvest sprouting presented by CD 1440 and Vintecinco ORS, respectively (De Sousa & Caierão, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The cultivar Frontana was introduced in 1940, descended from the crossing between Fronteira and Mentana, when it conferred resistance to leaf rust and pre-harvest sprouting. Cultivar Frontana is one of the best sources of tolerance pre-harvest sprouting (Franco et al, 2009;Santos et al, 2010;Nörnberg et al, 2015). The Ônix/CDFAPA 2001129 and Vanguarda/Temu 2624-00, parents are responsible for good tolerance to pre-harvest sprouting presented by CD 1440 and Vintecinco ORS, respectively (De Sousa & Caierão, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The line ND 674 and the cultivars Quartzo and Frontana were used as controls towards tolerance to pre-harvest sprouting. Frontana cultivar is one of the best wheat genotypes in terms of resistance to pre-harvest germination (Bassoi et al, 2006;Franco et al, 2009;Nörnberg et al, 2015). Quartzo cultivar was classified as moderately tolerant to tolerant to PHS (Nörnberg et al, 2015), and the PHS tolerance of the wheat line ND 674 was reported by Dr. L. Okuyama (personal communication).…”
Section: Materials Studiedmentioning
confidence: 98%
“…However, PHS tolerant white grain wheat genotypes are also known, which include AUS1408 (Mares, 1987) and CN19055 (Hucl and Matus-Cadiz, 2002). Following parameters are generally used for estimating the level of PHST: PHS index, falling number, germination index and alpha amylase activity (Nörnberg et al 2015;Shorinola et al 2016). Among cereals, in wheat alone, ~50 QTL interval mapping studies involving ~40 mapping populations have already been conducted leading to identi cation of as many as >250 QTLs for PHST, which also included hexaploid synthetic wheats, tetraploid durum wheats and diploid einkorn wheats (see review by Gupta et al 2020).…”
Section: Introductionmentioning
confidence: 99%